Correlation Between Chronic Tinnitus Distress and Symptoms of Depression: A Systematic Review - Meijers, Sebastiaan M.; Rademaker, Maaike; Meijers, Rutger L.; Stegeman, Inge; Smit, Adriana L. (Frontiers in Neurology, 2022)
Objectives In this systematic review, we aim to evaluate the evidence regarding the correlation between tinnitus distress and the severity of depressive symptoms in patients with chronic tinnitus. Also, the prevalence of clinically relevant depressive symptoms scores in patients with chronic tinnitus was evaluated. Methods We performed a systematic review in PubMed, EMBASE, and the Cochrane library in June 2021 using the terms “depression” and “tinnitus,” and their synonyms, following PRISMA guidelines. Studies were selected on relevance and critically appraised regarding risk of bias using the Newcastle–Ottowa Quality Assessment Scale. Results A total of 1,912 articles were screened on title and abstract after the removal of the duplicates. Eventually, 33 (1.5%) articles were included for the final analysis. Only cross-sectional cohort studies and case–control studies with a low level of evidence and a high risk of bias due to the study design and patient selection were found. Statistically significant correlations between the experienced tinnitus distress and depressive symptoms were reported in 31 out of 33 studies. Clinically relevant depression scores had a prevalence of 4.6–41.7%. Conclusions In this systematic review, in which mostly cross-sectional studies were included, a statistically significant correlation was found between the experienced tinnitus distress and the reported severity of symptoms of depression in patients with chronic tinnitus. A wide range of clinically relevant depression scores were reported in included studies. Due to the high risk of bias of included studies it is not possible to provide a definite answer on the existence of this relationship. Future population-based studies are necessary to provide more clarity.